Methionine addition to weanling pig diets - Ong, Tze-chow; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three growth trials and two metabolism trials utilizing 236 pigs were conducted to evaluate the effects of amino acids additions to weanling pig diets and to estimate the methionine requirement of weanling pigs using growth and nitrogen retention as criteria. From these results, it was concluded that the total sulfur amino acid requirement of weanling pigs does not exceed 0.56% of the diet. Addition of methionine to a lysine supplemented 18% protein corn or sorghum-soybean meal did not improve pig performance.
Keywords: Swine; Methionine; Weanling pigs